Analisis Pengakuan Pendapatan Jasa Konstruksi PadaCV. Indarchi Architect Team Klaten - Pramurti, Fina Setya (2016)
This study aims to mengtahui suitability of recognition of revenue contained in the CV. INdARCHI ARCHITECT TEAM Klaten with financial accounting standards SFAS No. 34 tentag construction contracts. This thesis is prepared using descriptive method. The data used in this research is secondary data, with data collection through the documentation, observation, interviews. Based on the results of comparison in revenue journal entries, as well as the effect on revenue which the completed contract method of revenue that results do not reflect the real situation in different companies with the percentage of completion method, revenues derived reflect the true financial condition of corporations. With the above research, the authors conclude companies use revenue recognition method that is not in accordance with the accounting standards of SFAS No. 34 on construction contracts so that revenue can be realized and get the highest credit worthy financial information to the financial statements.